KEPERCAYAAN MEREK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR KAWASAKI KLX DI KABUPATEN MERANGIN - Yudhi Novriansyah; Muhammad Asman; Isman Isman (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
The purpose of this research was to determine: (1) The Effect of Brand Trust on Purchasing Decision Kawasaki Motorcycle Consumers in Kabupaten Merangin . (2) The Effect of Price Perception on Purchasing Decision Kawasaki Motorcycle Consumers in Kabupaten Merangin. (3) The effect of Brand Trust and Price Perception on Purchasing Decision Kawasaki Motorcycle Consumers in Kabupaten Merangin. The method in this study uses quantitative methods. The data collection method uses questionnaires, interviews, observations, and documentation. Meanwhile, the data analysis used descriptive statistical analysis, data instrument test, classical assumption test, multiple regression line analysis, and multiple determinant coefficient (R2). The results showed that: (1) There was a significant effect of Brand Trust on Purchasing Decision Kawasaki Motorcycle Consumers in Kabupaten Merangin. (2) There is a significant effect of Price Perception on Purchasing Decision Kawasaki Motorcycle Consumers in Kabupaten Merangin. (3)There is a significant effect of Brand Trust and Price Perception on Purchasing Decision Kawasaki Motorcycle Consumers in Kabupaten Merangin. The result of (R²) poin 0,679 show that Independent variables can explain 67,9% purchasing decision and remaining 32,1% influence by other variable out of this research.